A Subject Review on a Some Analytical Methods for the Determination of Chloroquine and Hydroxychloroquine Drugs - Mahmood, Ali Khalil; Al-Janabi, Khalid Waleed S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
Chloroquine and Hydroxychloroquine drugs are widely prescribed for malaria disease. Since the end of 2019, humans have been under threat due to a disease called (COVID-19), which was first reported in China. Many methodical approaches have been reported to quantify chloroquine and hydroxychloroquine in blood, urine, plasma, serum, and pharmaceutical dosage form. Some of these techniques are spectrophotometry, liquid chromatography with a mass detector, gas chromatography, and ultra-performance, high-performance liquid chromatography (HPLC), in addition to electrochemical methods. This literature review discusses various analytical methods for the determining hydroxychloroquine and chloroquine.